Myocardial Infarction in Patients with and without COVID-19: Comparisons of Characteristics, Clinical Courses, and Outcomes - Hossein Sheibani; Mehran Gheshlaghi; Somayeh Shah Hosseini; Mojgan Javedani Masroor; Salman Daliri (Journal of Tehran University Heart Center, 2023)
Background: COVID-19 has rapidly become a global health emergency. This infection can cause damage to various organs. Injury to myocardial cells is one of the salient manifestations of COVID-19. The clinical course and outcome of acute coronary syndrome (ACS) are influenced by various factors, including comorbidities and concomitant diseases. One of these acute concomitant diseases is COVID-19, which can affect the clinical course and outcome of acute myocardial infarction (MI).